DIALEK FUKUI DALAM ANIME CHIHAYAFURU KARYA YUKI SUETSUGU - Ayu Retno Nadia; Arza Aibonotika; Intan Suri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: There are many different dialects in Japan. One of them is Fukui dialect. Fukui dialect is part of the Hokuriku dialect located in Fukui Prefecture, Chubu Region, Honshu Island. The grammar of Fukui dialect in many aspects reflects the Kansai dialect. Fukui dialect has a characteristic that there is a distinctive intonation that often appears at the end of a sentence, and accent is not a determinant of word meaning like most other dialects. The problem in this study is how the Fukui dialect is seen morphologically and it’s equivalent in standard Japanese. The research data is taken from the Chihayafuru anime by Yuki Suetsugu. Research result will be collected and analyzed. The result of this study found 20 data containing the suffix, negation, adverbial, adversative, demonstrative, and adjective.Key Words: Fukui dialect, morphology.